Does the Labrador-Québec border area of the Rae (Churchill) Province preserve vestiges of an Archean history? - Ryan, Bruce (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary This paper presents new data from an area ofthe Rae (eastern Churchill) Province where migmatite and gabbro-anorthosite complexes are intruded by metamorphosed diabase dykes. The pre-dyke rocks are lithologically comparable to Archean components in the Nain Province and may be correlative with them; the dykes may be equivalents of the Eariy Proterozoic dyke swarms of the Nain Province. It is proposed that this area comprises Archean crust that has escaped pervasive Early Proterozoic structural overprint, but was affected by the prevailing metamorphism. Preservation of these types of relationships may be more widespread in the Rae Province than presently recognized. Some tectonic implications of the data are discussed.